Soft Power in Iran's Foreign Policy - Tahseen Wsu Abdullah; Ahmed Babakr Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This research intends to analyze the concept of soft power within the framework of international relations. The concept of soft power as a modern issue in the field of international relations has in a short period of time gained great importance and has become an important tool in foreign policy of countries. It means that in the current era, this concept consists of one of the main pillars of foreign policy of the state. Iran, as a state with culture and old civilization, has also been reflected as a regional lying force in its foreign policy as a tool. In this context, the research is discussing the main tools that Iran relies on soft power in foreign policy. In addition to discussing the opportunity to use soft force in Iran's foreign policy, the research also discusses the problems and challenges facing Iran's foreign policy in its implementation.